Convective drying of highly shrinkable vegetables: New method on obtaining the parameters of the reaction engineering approach (REA) framework. (September 2021) - Yang, Shilei; Liu, Tao; Fu, Nan; Xiao, Jie; Putranto, Aditya; Chen, Xiao Dong
Abstract: Accurate modeling of fruits and vegetables is difficult due to complications like non-regular shrinkage, wrinkling and skin formation. Comprehensively capturing these changes remain difficult. An interesting pathway through a rearranged set of heat and mass transfer equations to obtain the parameters for the drying kinetics model of the lumped reaction engineering approach (L-REA) is demonstrated. This approach allows the obtainment of REA parameters without worrying about shrinkage in the first place. Carrot, typical of a highly shrinkable vegetable, was dried at temperatures of 43, 55 and 63 °C and a fixed air velocity of 1.5 m/s. The REA parameters reveal a slightly lower additional activation energy compared with that from the classical approach. It can be seen that all moisture content and temperature profiles agree well with experimental data supported by R 2 higher than 0.9959 for moisture and 0.9837 for temperature which validates the proposed new approach is highly feasible for modeling of highly shrinkable vegetables. This work demonstrates the flexibility of the REA framework in avoiding interwinding issues with shrinkage data accuracy and the obtainment of REA parameters when testing highly shrinkable materials. Highlights: A new pathway for obtaining REA parameters for highly shrinkable vegetables is demonstrated. Obtaining the REA parameters without involving surface area information is outlined. The REA model with accurate data on surface area predicts well the temperature-time and moisture-time profiles.